Método do Ó e o SM-LEGO: ferramentas para a educação musical com acessibilidade - Bisogno, Rafael Ecke (2023)
The search for new pedagogical practices to reduce the difficulty in the musical education process has resulted in the growth of the use of new technologies. Besides, these specialized methodologies are capable of bringing advantages to the teaching process. In this context, the present research proposes the use of an alternative musical notation system, called Do Ó Method, to assist in the process of teaching and learning music. This notation system allows the reading and writing of a rhythmic pattern without the need for students to have previous knowledge of music theory. This research has a quantitative approach supported by a qualitative approach. The experimental, obtained in the application of an experiment to validate the Do Ó Method, served as a basis for the development of a computational tool called SM-LEGO (Simple Method-LEarnig GOals). SM-LEGO performs the translation of a rhythmic pattern, written in a traditional score, to the Do Ó Method notation, allowing the user to visualize the translation result in the program interface, save it in a new file output, as well as perform the printing of 3D objects, called MusicLEGO. MusicLEGO pieces can be build on a board and their reading can even be performed using the tactile system. This feature expands the use of the Do Ó Method, enabling the use of these pieces by people who are blind or have low vision. Through the evaluation experiment, the Do Ó Method, SM-LEGO, and MusicLEGO pieces were established as educational tools. We conclude that these tools can be used in music teaching for people with and without Special Educational Needs (SEN), as well as in music education in a playful way. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001.